1998
DOI: 10.1002/(sici)1099-1417(1998110)13:6<549::aid-jqs394>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Heinrich event 1 in the British Isles

Abstract: In the north Irish Sea basin (ISB), sedimentary successions constrained by AMS 14 C dates obtained from marine microfaunas record three major palaeoenvironmental shifts during the last deglacial cycle. (i) Marine muds (Cooley Point Interstadial) dated to between 16.7 and 14.7 14 C kyr BP record a major deglaciation of the ISB following the Late Glacial Maximum (LGM). (ii) Terminal outwash and ice-contact landforms (Killard Point Stadial) were deposited during an extensive ice readvance, which occurred after 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(71 citation statements)
references
References 60 publications
1
70
0
Order By: Relevance
“…17D), is consistent with aspects of the reconstruction by Salt and Evans (2004) (their stages F and G). Renewed, climatically-driven ice sheet growth over northeast Ireland during the Killard Point Stadial has been suggested by McCabe et al (1998), and is supported by recent cosmogenic exposure ages of 15.6 10 Be ka BP from moraine sequences in north-western Ireland .…”
Section: Towards a Regional Synthesismentioning
confidence: 69%
See 3 more Smart Citations
“…17D), is consistent with aspects of the reconstruction by Salt and Evans (2004) (their stages F and G). Renewed, climatically-driven ice sheet growth over northeast Ireland during the Killard Point Stadial has been suggested by McCabe et al (1998), and is supported by recent cosmogenic exposure ages of 15.6 10 Be ka BP from moraine sequences in north-western Ireland .…”
Section: Towards a Regional Synthesismentioning
confidence: 69%
“…17B,C,D) (Knight, 2002) and a variety of inverse ice sheet models reconstruct an ice ridge over the North Channel linking the Southern Uplands and Lough Neagh dispersal centres during, and following, the LGM (e.g Boulton et al, 1991Boulton et al, , 2002. (McCabe et al, 1998;McCabe and Clark 2003;McCabe et al, 2007a). We speculate that the strong westward ice flow during stage C (Fig.…”
Section: Towards a Regional Synthesismentioning
confidence: 84%
See 2 more Smart Citations
“…At glacial maximum it has been argued that the peninsula was overridden by the main Scottish Ice Sheet, and during deglaciation a series of ice streams crossed the area, until final disappearance of the ice sheet toward the end of the Lateglacial Period (Charlesworth, 1926, Kerr, 1982, McCabe et al, 1998, Salt & Evans, 2004, Bradwell et al, 2008. Three decades ago, it was suggested that high-arctic marine deposits formerly seen in two claypits in SW Scotland were possible representatives of the high-arctic Errol Clay Formation of eastern Scotland, and were thus of Devensian lateglacial age (Peacock, 1975).…”
Section: Introductionmentioning
confidence: 99%